Plastic mulching and crop type govern the vertical distribution and composition of microplastics in a major agricultural irrigation system - Xuezheng Yu; Weiying Feng; Liu Wang; Yuxin Deng; Chia Min Ho; Yunping Han; Qingfeng Miao; Meng Zhao; José Manuel Gonçalves; Sundaravelpandian Kalaipandian (Environmental Research, 2026)

ODARRL: Obstacle- and Disturbance-Aware End-to-End Residual Reinforcement Learning for Underwater Robot Trajectory Tracking with Obstacle Avoidance - Linghan Meng; Zebin Huang; Qingfeng Yao; Yunxiu Zhang; Qifeng Zhang (Journal of Marine Science and Engineering, 2026)
ROVs are essential for marine exploration and underwater operations, yet conventional teleoperation relies heavily on skilled human operators, and many autonomous methods stop at high-level planning rather than low-level actuation, limiting robustness in disturbed and cluttered environments. This paper proposes ODARRL, an obstacle- and disturbance-aware sensor-to-thruster (ST) end-to-end residual reinforcement learning framework for safe trajectory execution of underwater robots. Using a three-stage curriculum, ODARRL first acquires a basic policy from MPC demonstrations in a static obstacle-free environment, then improves disturbance-robust tracking under random currents, and finally extends to scenarios involving both currents and obstacles. A Dual-Horizon Attention Disturbance Encoder is further designed to capture current-related features from long- and short-term histories, which are fused with robot states and reference information as the input to the ST end-to-end policy. Experiments in Marine Gym with BlueROV2 Heavy demonstrate that ODARRL achieves more stable and robust trajectory tracking under random currents, reducing the mean total tracking error by 69.3%, 31.9%, 45.8%, 73.0% and 25.8% relative to the MPC-imitation policy, PPO, SAC, A2C and VNRS-SAC, respectively. With obstacles introduced, curriculum-initialized policies also exhibit higher path progress and more stable task completion during obstacle-avoidance training.

AI-designed crop populations for sustainable intensification - Ning Luo; Junhan Wang; Morten Graversgaard; Renan C. Umburanas; De Li Liu; Qirui Li; Jonathan Storkey; Simon Willcock; Pu Wang; Qingfeng Meng (Trends in Plant Science, 2026)

Defect-mediated rigid-flexible coupled architecture for upcycling of spent O3-type sodium-ion cathodes - Qingfeng Liu; Jinhua Shi; Fanbin Hu; Zitong Fei; Yun Shen; Haigang Dong; Qi Meng; Peng Dong; Yingjie Zhang (Chemical Engineering Journal, 2026)

Improvement of probiotic tolerance to hyperosmotic environments by whey protein-citrus pectin conjugate: effect on the physicochemical, structural, survival of probiotic microencapsulation - Xuan Lu; Ning Zhang; Jingru Chen; Xinyi Li; Suo Zheng; Fei Liu; Qingfeng Ban; Xiangchen Meng (Food Research International, 2026)

High-performance, durable bamboo conductive macrofibers based triboelectric nanogenerator for stable harvesting water wave energy - Jiaqi Liao; Qingyu Meng; Wenwen Zhu; Wenhao Xu; Yang Peng; Shitao Shi; Zewei Ye; Chencong Liu; Qingfeng Sun; Xiaoping Shen (Chemical Engineering Journal, 2026)

Prediction of in situ seafloor sediment sound speed with machine learning - Mujun Chen; Linqing Zhang; Xinfeng Hu; Xiangmei Meng; Guangming Kan; Siyou Tong; Jingqiang Wang; Guanbao Li; Baohua Liu; Qingfeng Hua; Siqi Wu; Xiaobo Zhang (Journal of Oceanology and Limnology, 2026)

Stabilization mechanisms, cell density, and survival of probiotic encapsulation prepared with thiolated hyaluronic acid-whey protein complex: For potential colon targeting probiotic delivery system - Ning Zhang; Xuan Lu; Jingru Chen; Xinyi Li; Suo Zheng; Fei Liu; Qingfeng Ban; Xiangchen Meng (Food Research International, 2026)

Electronic structure reconstruction and interface anchoring for high-performance direct regeneration of spent LiFePO4 materials - Yuyun Li; Yuan Ping; Fanbin Hu; Changjiang Li; Jinhua Shi; Haigang Dong; Qingfeng Liu; Yingjie Zhang; Qi Meng; Peng Dong (Chemical Engineering Journal, 2026)

Two-phase structure optimization of Al-doped Ag1.995Te0.5S0.5 for improved mechanical and thermoelectric properties - Min Zhu; Xiao-Lei Shi; Hao Wu; Meng Li; Wei-Di Liu; De-Zhuang Wang; Liang-Cao Yin; Wen-Yi Chen; Yan Huang; Zhi-Gang Chen; Qingfeng Liu (Chemical Engineering Journal, 2026)

Impedance inversion of high-frequency Chirp sub-bottom profiles constrained by borehole data - Linqing Zhang; Xishuang Li; Lejun Liu; Xiangmei Meng; Qingjie Zhou; Kai Liu; Qingfeng Hua; Jingqiang Wang (Marine Georesources & Geotechnology, 2026)

Editorial Expression of Concern: HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Improvement of quercetin bioaccessibility by whey protein isolate/D-tagatose conjugates: Effect on the structural characterization through simultaneous rheological and FTIR techniques - Feifei Chen; Yao Meng; Yujie Lin; Qingfeng Ban; Fei Liu (Food Hydrocolloids, 2025)

Water and land use in China's food systems: Exploring potential mitigation strategies - Wenjun Shi; Hanlin Liu; Yosef Steinberger; Yuanchao Hu; Yang Yang; Qingfeng Meng; Guanghui Xie (Sustainable Production and Consumption, 2025)

Incorporating graphene quantum dots boosts thermoelectric performance of PEDOT:PSS films - Ting Wu; Xiao-Lei Shi; Yu-Yu Deng; Yuan-Meng Liu; Min Zhu; Wei-Di Liu; Meng Li; Fang Yue; Pei Huang; Zhi-Gang Chen; Qingfeng Liu (Chemical Engineering Journal, 2025)

High-performance thermoelectric PEDOT:PSS fiber bundles via rational ionic liquid treatment - Yu-Yu Deng; Xiao-Lei Shi; Ting Wu; Hao Wu; Yuan-Meng Liu; Min Zhu; Wei-Di Liu; Meng Li; Pei Huang; Qingfeng Liu; Zhi-Gang Chen (Chemical Engineering Journal, 2024)

Constructing local structure heterogeneity in AgNbO3-based antiferroelectrics: Achieving excellent anti-fatigue and energy storage properties - Shuaibing Gao; Zhihang Xu; Haolin Zeng; Meng Shen; Ye Zhu; Haitao Huang; Yongming Hu; Yunbin He; Qingfeng Zhang (Chemical Engineering Journal, 2024)

Benzo(a)pyrene exposure impacts cerebrovascular development in zebrafish embryos and the antagonistic effect of berberine - Ke Xu; Qian Wang; Ying Zhang; Yuehong Huang; Qingfeng Liu; Meng Chen; Chonggang Wang (Science of The Total Environment, 2024)

Unlocking maize yield potential through exploring canopy-root interactions with nature-based nutrient management - Yupeng Zhu; Junhao Wang; Yongjun Zhu; Han Lai; Ziren Qu; Jian Zhao; Dan Wei; Pu Wang; Qingfeng Meng (Field Crops Research, 2024)

Identifying and modelling the barriers to returns of end-of-life (EOL) heavy-duty machinery in Nigeria: A consumers’ perspective - Qingfeng Meng; Ukoha Kalu Okwara (Journal of Cleaner Production, 2024)

Microplastics increase the microbial functional potential of greenhouse gas emissions and water pollution in a freshwater lake: A metagenomic study - Tianyu Zhuo; Kehong Yu; Beibei Chai; Qingfeng Tang; Xia Gao; Jiamin Wang; Lixin He; Xiaohui Lei; Yang Li; Yuan Meng; Lifeng Wu; Bin Chen (Environmental Research, 2024)

Water stress combining weather condition shapes wheat yield and inter-annual yield variability: Field observations from a six-year study - Dan Wei; Beijing Tian; Qingzhao Wu; Haijiang Wang; Pu Wang; Qingfeng Meng (European Journal of Agronomy, 2024)

Applications of agent-based models for green development: a systematic review - Qingfeng Meng; Yu Ji; Zhen Li; Xin Hu; Heap-Yih Chong (Environment, Development and Sustainability, 2024)

How can the policy combination promote the development of green buildings? ---Analysis based on stage perspective - Xijie Ai; Qingfeng Meng; Heap-Yih Chong; Zhen Li; Tiantian Hao (Journal of Cleaner Production, 2024)

Thermodynamic design and analysis of air-liquefied energy storage combined with LNG regasification system - Qingfeng Jiang; Shiqing Wan; Chongyao Pan; Guozeng Feng; Huaibing Li; Hansheng Feng; Bo Meng; Jiayang Gu; Yunchu Feng (International Journal of Refrigeration, 2024)

Seafloor Sediment Acoustic Properties on the Continental Slope in the Northwestern South China Sea - Guanbao Li; Jingqiang Wang; Xiangmei Meng; Qingfeng Hua; Guangming Kan; Chenguang Liu (Journal of Marine Science and Engineering, 2024)
The acoustic properties of seafloor sediments on continental slopes play a crucial role in underwater acoustic propagation, communication, and detection. To investigate the acoustic characteristics and spatial distribution patterns of sediments on the continental slope, a geoacoustic experiment was conducted in the northwestern South China Sea. The experiment covered two sections: one crossing the shelf and slope in the downslope direction, and the other near the shelf break in the along-slope direction. In situ techniques, sediment sampling, and laboratory measurements were used to acquire data on sediment acoustic properties (such as sound speed and attenuation) and physical properties (including particle composition, density, porosity, and mean grain size). The experimental findings revealed several key points: (1) Acoustic properties of shallow water coarse-grained sediments and deep-sea sediments were higher when measured in the laboratory compared to in situ measurements. (2) Relationships between measured attenuation and physical properties, as well as between sound speed and mean grain size, showed deviations from previous empirical equations. (3) Sediment acoustic and physical properties exhibited significant variations in the downslope direction, while showing gradual variations in the along-slope direction. These variations can be attributed to sedimentary environmental factors such as material sources, hydrodynamic conditions, and water depth.

Can high-yielding maize system decrease greenhouse gas emissions largely while simultaneously enhancing economic and ecosystem benefits through the “Rhizobiont” concept? Evidence from field - Yupeng Zhu; Ziren Qu; Jian Zhao; Junhao Wang; Dan Wei; Qingfeng Meng (Science of The Total Environment, 2024)

Research on the interplay between green finance and manufacturing sustainability outcomes: insights for low-carbon economy in the post-COVID-19 era - Qingfeng Meng; Ukoha Kalu Okwara; Zhen Li (Environmental Science and Pollution Research, 2023)

Prediction Model of the Sound Speed of Seafloor Sediments on the Continental Shelf of the East China Sea Based on Empirical Equations - Guangming Kan; Junjie Lu; Xiangmei Meng; Jingqiang Wang; Linqing Zhang; Guanbao Li; Baohua Liu; Qingfeng Hua; Mujun Chen (Journal of Marine Science and Engineering, 2023)
Based on the data of the acoustic and physical properties of seafloor sediments obtained on the continental shelf area of the East China Sea (ECS), prediction equations of the sediment sound speed based on single and dual parameters were established, and the correlation of the sound speed with physical parameters was discussed. The results show that the sediment sound speed (c) is strongly correlated with water content (w), density (ρ), void ratio (e), mean grain size (Mz) and median grain size (Md), and the coefficient of determination R2 of the empirical regression equation is generally greater than 0.80, while the empirical regression equation coefficient of determination R2 of the compression coefficient (a) and compression modulus (E) are slightly lower, with 0.79 and 0.73, respectively. The coefficients of determination of the dual parameter regression equations between sediment sound speed with physical property parameters are generally higher than those of the single parameter equations, which are all higher than 0.90 indicating better prediction performance. The sensitivity of the physical parameters to the sound speed was analyzed, and the result shows that the sequence of sensitivity from high to low influence on sediment sound speed is void ratio, density, compressibility coefficient, median grain size and mean grain size. The prediction equations established in this study are a good extension and supplement to marine geoacoustic models and is of great significance for obtaining the acoustic properties of the seafloor sediments on the shelf of the East China Sea.

A personalized regression model for predicting thermal sensation based on local skin temperature in moderate summer conditions - Yun Qi; Rui Wang; Chaoyi Zhao; Chao Ding; Chenqiu Du; Jiazheng Zhang; Xuan Zhang; Xinchang Chen; Mingjie Zhang; Qingfeng Bie; Meng Ge (Energy and Buildings, 2023)

Enhancing maize yield through understanding the novel shoot-root interaction in morphology among hybrids with dense planting - Yupeng Zhu; Su Wang; Yunhao Li; Dan Wei; Ning Luo; Pu Wang; Qingfeng Meng (Field Crops Research, 2023)

Diverse water management in a preceding wheat crop does not affect maize yield but increases inter-annual variability: A six-year field study - Dan Wei; Ning Luo; Yupeng Zhu; Pu Wang; Qingfeng Meng (Field Crops Research, 2023)

Water replenishment to maize under heat stress improves canopy temperature and grain filling traits during the reproductive stage - Xinglong Wang; Ning Luo; Yupeng Zhu; Ye Yan; Haijiang Wang; Hejing Xie; Pu Wang; Qingfeng Meng (Agricultural and Forest Meteorology, 2023)

Trade openness, globalization, and natural resources management: The moderating role of economic complexity in newly industrialized countries - Xiuping Guo; Xianglei Meng; Qingfeng Luan; Yanhua Wang (Resources Policy, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Responses of Soil Humus Composition and Humic Acid Structural Characteristics to the Addition of Different Types of Biochar in Phaeozems - Qi Wang; Yingxue Zhu; Lianzhou Xu; Baiyang Chen; Chunzhu Liu; Xianfa Ma; Qingfeng Meng; Bing Liu; Zongwei Huang; Yusheng Jiao; Ye Yuan (Journal of Soil Science and Plant Nutrition, 2023)

Phenological responses of Bactrocera dorsalis (Hendel) to climate warming in China based on long-term historical data - Pumo Cai; Yunzhe Song; Litao Meng; Jia Lin; Mengting Zhao; Qingfeng Wu; Chuanpeng Nie; Yanyan Li; Qinge Ji (International Journal of Tropical Insect Science, 2023)
It is well accepted that the phenology of insects whose life activities are closely related to temperature is changing in response to global climate warming. To investigate the impacts of climate warming on the phenology of Bactrocera dorsalis (Hendel) across large temporal and spatial scales, this study collected historical data on the occurrence and population dynamic of this pest in China, and systematically explored its phenological responses. The results showed a delayed trend for the dates of first occurrence, end occurrence, population initial growth, and population peak of B. dorsalis in China during 40 years, and the changes of the latter two phenological parameters were significant. The mean temperature in spring and summer were the key climatic factors affecting the occurrence and population growth of B. dorsalis in China, respectively. Moreover, the B. dorsalis data in eastern, southern, central, and southwestern China showed spatial heterogeneity of phenological responses to climate warming at a regional scale. B. dorsalis phenology and their changing patterns with climate warming varied by geographical location. This study provides valuable information for future monitoring, prediction, and prevention of the oriental fruit fly in the context of climate warming.

Anti-swellable cellulose hydrogel for underwater sensing - Zhuyue Lan; Yuanyuan Wang; Ke Hu; Shitao Shi; Qingyu Meng; Qingfeng Sun; Xiaoping Shen (Carbohydrate Polymers, 2023)

How to effectively prevent alienation behavior of prefabricated construction developers: an optimization analysis of regulatory strategies - Xijie Ai; Qingfeng Meng; Zhen Li; Wenyao Liu (Environmental Science and Pollution Research, 2023)

Association of biomass fuel use with the risk of vision impairment among Chinese older adults: a cohort study - Ying Zhou; Minzhi Xu; Pan Ke; Hongkun Di; Yong Gan; Jing Feng; Xin Meng; Cheng Su; Qingfeng Tian; Zuxun Lu (Environmental Science and Pollution Research, 2023)

Alleviating groundwater depletion while realizing food security for sustainable development - Dan Wei; Xinglong Wang; Ning Luo; Yupeng Zhu; Pu Wang; Qingfeng Meng (Journal of Cleaner Production, 2023)

Effect of Maillard reaction conditions on the gelation and thermal stability of whey protein isolate/d-tagatose conjugates - Yao Meng; Xiao Zhao; Yunqing Jiang; Qingfeng Ban; Xibo Wang (Food Chemistry, 2023)

Development of a recombinant adenovirus-vectored vaccine against both infectious hematopoietic necrosis virus and infectious pancreatic necrosis virus in rainbow trout (Oncorhynchus mykiss) - Shouhu Li; Xincang Li; Rui Yuan; Xiaoxue Chen; Shouxu Chen; Yu Qiu; Qingfeng Yang; Meng Wang; Jiangao Shi; Shuo Zhang (Fish & Shellfish Immunology, 2023)

Long-term effects of cattle manure application on the soil aggregate stability of salt-affected soil on the Songnen Plain of North-Eastern China - Shuo Zhao; Fei Yu; Cheyu Zhai; Rui Zhong; Ying Zhao; Yong Wang; Juan Zhang; Qingfeng Meng (Journal of Soils and Sediments, 2023)

Pricing and promotion efforts strategies of dual-channel green supply chain considering service cooperation and free-riding between online and offline retailers - Mengwan Li; Miyuan Shan; Qingfeng Meng (Environment, Development and Sustainability, 2022)

Mechanism of molecules crosstalk and the critical role of jasmonic acid on triterpenoid synthesis in Cyclocarya Paliurus cells under Aspergillus niger elicitor - Meng Wang; Daobang Tang; Qiongqiong Xiong; Jiguang Chen; Xiaoxiang Xu; Qingfeng Zhang; Jingen Li; Xiangju Zhou; Zhongping Yin (Journal of Plant Biochemistry and Biotechnology, 2022)

Dual-channel recycling e-waste pricing decision under the impact of recyclers’ loss aversion and consumers’ bargaining power - Zhen Li; Jia Zhao; Qingfeng Meng (Environment, Development and Sustainability, 2022)

High-Frequency Dependence of Acoustic Properties of Three Typical Sediments in the South China Sea - Jingqiang Wang; Zhengyu Hou; Guanbao Li; Guangming Kan; Baohua Liu; Xiangmei Meng; Qingfeng Hua; Lei Sun (Journal of Marine Science and Engineering, 2022)
The acoustic characteristics of three fine-grained sediments (silty sand, silt, silty clay) in the South China Sea (SCS) were measured and analyzed at high frequency range of 27–247 kHz. The measurement results show that the sound speed dispersion is a positive linear relation at the measured frequency range, and the attenuation follows nonlinear frequency dependence, α = kfn, where n ranges from 0.59 to 0.85 for the three different sediments in the SCS. The frequency dependence of sound speed and attenuation were compared with the published literature. It was found that for silty clay, clayey silt, silt, and silty sand, the dispersion characteristics of these four sediments are basically consistent; in general, the dispersion of coarse particles is significant, and that of fine particles is weak, and permeability is the key parameter that determines the inflection point of high frequency to low frequency. By modeling these sediments with the Biot–Stoll model, it was found that the Biot–Stoll model can better predict the frequency-dependent characteristics of sound attenuation in a high-frequency band under the matching constraints of sound speed dispersion characteristics, indicating that the Biot–Stoll model has good applicability to different types of sediments in a high-frequency band.

Late Jurassic adakitic ore-bearing granodiorite porphyry intrusions in the Xiaokele porphyry Cu (–Mo) deposit, Northeast China: implications for petrogenesis and tectonic setting - Yonggang Sun; Bile Li; Zhonghai Zhao; Qingfeng Ding; Fanbo Meng; Xusheng Chen; Ye Qian; Yujin Li (Acta Geochimica, 2021)

Dynamic reward and penalty strategies of green building construction incentive: an evolutionary game theory-based analysis - Qingfeng Meng; Yingying Liu; Zhen Li; Changzhi Wu (Environmental Science and Pollution Research, 2021)

Relationships between the sound speed ratio and physical properties of surface sediments in the South Yellow Sea - Guanbao Li; Jingqiang Wang; Xiangmei Meng; Baohua Liu; Guangming Kan; Guozhong Han; Qingfeng Hua; Yanliang Pei; Lei Sun (Acta Oceanologica Sinica, 2021)

Distribution of water-stable aggregates under soil tillage practices in a black soil hillslope cropland in Northeast China - Lei Yan; Xuexin Jiang; Xiaonan Ji; Liting Zhou; Siying Li; Chen Chen; Peiye Li; Yuanchen Zhu; Tianhao Dong; Qingfeng Meng (Journal of Soils and Sediments, 2020)

Additional application of aluminum sulfate with different fertilizers ameliorates saline-sodic soil of Songnen Plain in Northeast China - Meng Zhou; Xiaobing Liu; Qingfeng Meng; Xiannan Zeng; Jizhou Zhang; Dawei Li; Jie Wang; Weiling Du; Xianfa Ma (Journal of Soils and Sediments, 2019)

Sound speed dispersion characteristics of three types of shallow sediments in the southern yellow sea - Guangming Kan; Baohua Liu; Jingqiang Wang; Xiangmei Meng; Guanbao Li; Qingfeng Hua; Lei Sun (Marine Georesources & Geotechnology, 2018)

Experimental study of the ballast in situ sediment acoustic measurement system in South China Sea - Jingqiang Wang; Guanbao Li; Baohua Liu; Guangming Kan; Zhiwen Sun; Xiangmei Meng; Qingfeng Hua (Marine Georesources & Geotechnology, 2018)

Increasing concurrent drought and heat during the summer maize season in Huang–Huai–Hai Plain, China - Lijun Wang; Shuhua Liao; Shoubing Huang; Bo Ming; Qingfeng Meng; Pu Wang (International Journal of Climatology, 2018)
Although an individual climate event may not be severe, the concurrence of climate events could have a significant impact on crop production. Investigating concurrent climate extremes during crop growth is important to formulate corresponding strategies for crop production. To assess the occurrence risk of concurrent drought and heat events in the Huang–Huai–Hai Plain (HHHP), China during the summer maize season, we analysed the temporal and spatial patterns of precipitation, standardized precipitation evapotranspiration index (SPEI), drought frequency, and extreme degree days (EDD) during the critical growth period. We used daily data from 41 meteorological stations in the region from 1980 to 2015. We determined that concurrent drought and heat events increased from northeast to southwest. The combined events mainly occurred during the vegetative period, and they significantly increased in 2006–2015 relative to 1981–1990. The spatial distribution of precipitation increased from northwest to southeast, while drought displayed no significant trends. The EDD displayed a rising trend and was intensified after 2000 in different growth periods. Its spatial distribution increased from east to west during the vegetative period and from northeast to southwest during the reproductive period. Although we focused on the combined extreme events for maize in HHHP, similar phenomenon should receive more attention in globally important crop areas and other ecosystems.

Associations of MMP-2 −1306 C/T and MMP-9 −1562 C/T polymorphisms with breast cancer risk among different populations: a meta-analysis - Meng Han; Qingfeng Yang; Kai Feng; Rongping Li; Jia Ren; Liguang Wei (Genes & Genomics, 2017)

Distribution of carbon and nitrogen in water-stable aggregates and soil stability under long-term manure application in solonetzic soils of the Songnen plain, northeast China - Qingfeng Meng; Yuting Sun; Jing Zhao; Lianren Zhou; Xianfa Ma; Meng Zhou; Wei Gao; Guangcheng Wang (Journal of Soils and Sediments, 2014)

The benefits of recent warming for maize production in high latitude China - Qingfeng Meng; Peng Hou; David B. Lobell; Hongfei Wang; Zhenling Cui; Fusuo Zhang; Xinping Chen (Climatic Change, 2014)

Complete genome sequence of Escherichia coli O157:H7 lytic phage JL1 - FengGuang Pan; Han Wu; JinHua Liu; YongXing Ai; XianMei Meng; RiZeng Meng; Qingfeng Meng (Archives of Virology, 2013)

Closing the yield gap could reduce projected greenhouse gas emissions: a case study of maize production in C hina - Zhenling Cui; Shanchao Yue; Guiliang Wang; Qingfeng Meng; Liang Wu; Zhiping Yang; Qiang Zhang; Shiqing Li; Fusuo Zhang; Xinping Chen (Global Change Biology, 2013)
Although the goal of doubling food demand while simultaneously reducing agricultural environmental damage has become widely accepted, the dominant agricultural paradigm still considers high yields and reduced greenhouse gas ( GHG ) intensity to be in conflict with one another. Here, we achieved an increase in maize yield of 70% in on‐farm experiments by closing the yield gap and evaluated the trade‐off between grain yield, nitrogen (N) fertilizer use, and GHG emissions. Based on two groups of N application experiments in six locations for 16 on‐farm site‐years, an integrated soil‐crop system ( HY ) approach achieved 93% of the yield potential and averaged 14.8 Mg ha −1 maize grain yield at 15.5% moisture. This is 70% higher than current crop ( CC ) management. More importantly, the optimal N rate for the HY system was 250 kg N ha −1 , which is only 38% more N fertilizer input than that applied in the CC system. Both the N 2 O emission intensity and GHG intensity increased exponentially as the N application rate increased, and the response curve for the CC system was always higher than that for the HY system. Although the N application rate increased by 38%, N 2 O emission intensity and the GHG intensity of the HY system were reduced by 12% and 19%, respectively. These on‐farm observations indicate that closing the yield gap alongside efficient N management should therefore be prominent among a portfolio of strategies to meet food demand while reducing GHG intensity at the same time.

Soil quality in east coastal region of China as related to different land use types - Qingfeng Meng; Jingsong Yang; Rongjiang Yao; Guangming Liu (Journal of Soils and Sediments, 2013)

Daidzein Induced Apoptosis via Down-Regulation of Bcl-2/Bax and Triggering of the Mitochondrial Pathway in BGC-823 Cells - Shuyao Tang; Jing Hu; Qingfeng Meng; Xuesong Dong; Kaifu Wang; Yuebin Qi; Chao Chu; Xiaochuan Zhang; Limin Hou (Cell Biochemistry and Biophysics, 2013)

HP-β-CD-PLGA nanoparticles improve the penetration and bioavailability of puerarin and enhance the therapeutic effects on brain ischemia–reperfusion injury in rats - Hai-quan Tao; Qingfeng Meng; Ming-hui Li; Hui Yu; Mei-fang Liu; Dan Du; Shou-li Sun; Hai-cheng Yang; Yan-ming Wang; Wei Ye; Li-zhuang Yang; Da-ling Zhu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Inhibition of focal adhesion kinase induces apoptosis in human gastric carcinoma cells (SGC-7901) - Jiyou Li; Qingfeng Meng; Yu Sun; Huadong Qing (Molecular Biology Reports, 2013)

Overexpressed mutant optineurin(E50K) induces retinal ganglion cells apoptosis via the mitochondrial pathway - Qingfeng Meng; Jia Lv; Hongyan Ge; Lu Zhang; Fei Xue; Yuanmao Zhu; Ping Liu (Molecular Biology Reports, 2012)

Transgenic mice with overexpression of mutated human optineurin(E50K) in the retina - Qingfeng Meng; Zheng Xiao; Huiping Yuan; Fei Xue; Yuanmao Zhu; Xinrong Zhou; Binbin Yang; Jingbo Sun; Bo Meng; Xian Sun; Fang Cheng (Molecular Biology Reports, 2012)